Peran Pendidikan Agama Kristen dalam Pembentukan Karakter dan Nilai-Nilai Moral pada Generasi Muda - Dyulius Thomas Bilo; Jhon Melvin (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
To address the moral extremism that often occurs among adolescents, strengthening education is crucial today. Christian Religious Education plays a crucial role in instilling an understanding of character, ethics, spiritual values, and noble moral habits. This research uses a qualitative descriptive method, with thorough literature exploration and data analysis. The study of Christian Religious Education is expected to be a companion that provides understanding, appreciation, and honest living based on Christian duties and values. This task is drawn from sources such as the Holy Scriptures, the life of Jesus Christ, and the ethical values ​​contained in Christianity. In this context, Christian Religious Education aims to produce a generation that is obedient to God and grows in faith and good moral values. Therefore, Christian Religious Education has a significant, very complex, and interconnected role. Its task is not only to provide spiritual understanding, but also to shape the character and morals of the younger generation so that they can face the challenges of the times with strong and sustainable moral values.